Targeted Delivery of Bioactive Molecules for Vascular Intervention and Tissue Engineering - Strobel, Hannah A.; Qendro, Elisabet I.; Alsberg, Eben; Rolle, Marsha W. (Frontiers in Pharmacology, 2018)
Cardiovascular diseases are the leading cause of death in the United States. Treatment often requires surgical interventions to re-open occluded vessels, bypass severe occlusions, or stabilize aneurysms. Despite the short-term success of such interventions, many ultimately fail due to thrombosis or restenosis (following stent placement), or incomplete healing (such as after aneurysm coil placement). Bioactive molecules capable of modulating host tissue responses and preventing these complications have been identified, but systemic delivery is often harmful or ineffective. This review discusses the use of localized bioactive molecule delivery methods to enhance the long-term success of vascular interventions, such as drug-eluting stents and aneurysm coils, as well as nanoparticles for targeted molecule delivery. Vascular grafts in particular have poor patency in small diameter, high flow applications, such as coronary artery bypass grafting (CABG). Grafts fabricated from a variety of approaches may benefit from bioactive molecule incorporation to improve patency. Tissue engineering is an especially promising approach for vascular graft fabrication that may be conducive to incorporation of drugs or growth factors. Overall, localized and targeted delivery of bioactive molecules has shown promise for improving the outcomes of vascular interventions, with technologies such as drug-eluting stents showing excellent clinical success. However, many targeted vascular drug delivery systems have yet to reach the clinic. There is still a need to better optimize bioactive molecule release kinetics and identify synergistic biomolecule combinations before the clinical impact of these technologies can be realized.